2014
DOI: 10.1038/jid.2013.326
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Response to Biologic Treatment: Perspective for Psoriasis

Abstract: Psoriasis treatment responses are affected by patient characteristics. However, the literature does not contain reviews of factors that affect the response to biologic therapies. We therefore performed a comprehensive literature search to identify papers describing demographic, lifestyle, and clinical factors associated with response to biologic drug therapy in psoriatic patients. We found that age, gender, ethnicity, alcohol consumption, smoking, geographic location, age at diagnosis, duration and severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 34 publications
9
90
5
1
Order By: Relevance
“…The possibility of pregnancy in women of child-bearing age might be a reason for reduced usage of biologics in women. With regards to response to biologics, gender was not a predicting factor to response, either in our study or in other larger meta-analysis (10). On the other hand, naïvety to biologics was an important factor, as our naïve patients did not only have worse psoriasis at baseline, but even showed better PASI improvement at 3 and 6 months in comparison with non-naïve patients.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The possibility of pregnancy in women of child-bearing age might be a reason for reduced usage of biologics in women. With regards to response to biologics, gender was not a predicting factor to response, either in our study or in other larger meta-analysis (10). On the other hand, naïvety to biologics was an important factor, as our naïve patients did not only have worse psoriasis at baseline, but even showed better PASI improvement at 3 and 6 months in comparison with non-naïve patients.…”
Section: Discussioncontrasting
confidence: 50%
“…A superior response to TNF-α was also noted in naïve rheumatoid arthritis patients in comparison with their non-naïve counterparts (14). Nevertheless, similar findings were inconsistently published in the literature and the reports of conflicting results gave rise to the need for more studies investigating that aspect (10). No significant correlation was found between PASI, BMI or age, on the one hand, and type of biologics, on the other hand.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a recent analysis by Edson-Heredia et al 11 examining which demographic or clinical factors are associated with response to biologic therapy in psoriasis, it was found that BMI had the strongest effect across studies. A phase III trial of ustekinumab for psoriasis found that higher body weight was an independent predictor of response to ustekinumab at week 28 (p<0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…A high BMI is a known predictor for discontinuation of biologics (Carrascosa et al, 2014b;Di Lernia et al, 2012;Edson-Heredia et al, 2014;Naldi et al, 2008). Ustekinumab is used in two doses: 45mgs in patients weighing ≤ 100 Kgs and 90mgs in those > 100 Kgs, whilst adalimumab and etanercept are used as fixed doses irrespective of body weight.…”
Section: Probable Factors Accounting For Survival With Biologicsmentioning
confidence: 99%